(untitled) (The Pakistan Development Review, 2011)
The issue of the implication of interlinkage of factor markets on the allocative efficiency level of the farm households deserves a special attention in the light of the controversy among two distinct schools of thought: the Neoclassical and the Marxist. An attempt has been made in the paper to measure allocative and cost efficiencies of the interlinked holding vis-à-vis a comparable group of non-interlinked holding in the framework of Data Envelopment Analysis. Empirical evidence establishes the Neo-classical proposition that interlinked factor markets can be considered as one of the “efficiency improving institutional change” in rural agrarian economy. JEL classification: D61, C87, Q14. Keywords: Interlinkage, Allocative Efficiency, Rural Credit, Data Envelopment Analysis